Analysis of Resilience of Education System in Higher Education Due to Covid-19 Pandemic in Indonesia: A Systematic Literature Review - Widiartha, Ida Bagus Ketut; Hwang, Jun-seok; Yoon, Hyoen-yeong; Pratiwi, Oktariani Nurul (Society of Visual Informatics, 2023)
This study discusses learning strategies resilience that can be used to improve learning outcomes during the current pandemic circumstances, which have limitations in face-to-face learning. Online learning has many limitations compared to offline one. However, it must keep running because one of the strategies against the SAR-Cov2 virus is to inhibit its spread by limiting direct contact with other people. The literature review is carried out with a protocol involving text mining tools to find the most widely used keywords and their relationships, which is then carried out by a snowball literature review to deepen these keywords. There are several findings from this study, namely (1) Three critical components that play a significant role in improving learning outcomes in the distance learning method, namely the role of students, lectures, and technology. (2) A framework must ensure that the other three components perform their functions properly and provide an effective learning environment. (3) Reward and punishment play a vital role in ensuring the framework is implemented as it should be. Integrating an effective learning environment with remuneration programs and teaching grants will encourage improvements in the learning process and increase the number of positive contents on the Internet. This learning environment can also be a model that supports independent learning activities - an independent campus, the Ministry of Education and Culture of the Republic of Indonesia's flagship program, and digital commercialization in the educational sphere.